Clinical Features of Cluster Headache: A Hospital-Based Study in Taiwan - Ko, Chien-An; Lin, Guan-Yu; Ting, Chi-Hsin; Sung, Yueh-Feng; Lee, Jiunn-Tay; Tsai, Chia-Kuang; Tsai, Chia-Lin; Lin, Yu-Kai; Ho, Tsung-Han; Yang, Fu-Chi (Frontiers in Neurology, 2021)
Most previous studies on cluster headache (CH) focus on Western populations. This study aimed to investigate the clinical characteristics of CH in a neurology outpatient population in Taiwan. A cross-sectional survey was conducted from July 2015 to June 2019 in a medical college affiliated with a tertiary care hospital (Tri-Service General Hospital) in Taiwan. All consecutive patients reporting headache as their chief complaint were asked to participate in a face-to-face interview with a qualified headache specialist and to complete a detailed self-administered questionnaire. The diagnosis of CH was made according to the Third edition of the International Classification of Headache Disorders. The subjects comprised 80 consecutive new CH patients (13 women and 67 men; ratio, 1:5). The mean age at presentation was 36.0 ± 10.8 years (range, 16–64 years), mean age at onset was 27.2 ± 12.1 years (range, 5–65 years), and mean time lag before diagnosis was 9.3 ± 10.5 years (range, 0–46.4 years). Of the total CH patients, 25.3% reported feelings of restlessness during headache episodes. A seasonal predilection was reported by 18% of the CH patients. The use of tobacco was the most common (44/80 patients). Chronic CH was only observed in 5% of the patients and only one patient (1.3%) reported both a positive family history for CH and aura. Features of CH in Taiwanese patients differed from that of Caucasian patients; a lower prevalence of chronic CH, positive family history of CH, and occurrence of aura may be less common in the former than in the latter.